Adult and Continuing Education in France - Schreiber-Barsch, Silke (Länderporträts, 2015)
"The English language volume offers a current stock-take of central areas in adult and vocational further education in France. The author Silke Schreiber-Barsch bases her work on various types of data and information. Beginning with historical developments, Schreiber-Barsch covers the topics of political, financial and institutional framework conditions, as well as offer, participation and teaching personnel. In closing, she outlines the current research status in terms of adult education and its role in the third level education system. The regional portrait offers well founded starting point and good orientation for getting to know the French system for adult and vocational further education."